Stability of T-DNA Integration in Phalaenopsis “Sogo Vivien” Transgenic Orchid Carrying 35S::Gal4::AtRKD4::GR - Endang Semiarti; Exsyupransia Mursyanti; Ahmad Suyoko; Faiza Senja Widya Perdana; Catharina Tri Widyastuti; Aditya Nur Subchan (Biology, Medicine, & Natural Product Chemistry, 2018)
Orchid is an elegant ornamental plant and favoured by the society. Phalaenopsis "Sogo vivien" is a mini-sized orchid with an interesting white-striped purple petals. This study was aimed to analyze the stability of the integration of embryonic gene carrier T-DNA from Arabidobsis AtRKD4 into the P. "Sogo vivien" genome produced in 2016. The study was conducted in 3 stages: 1) Transgenic plant phenotype analysis (1 year old); 2) Examination of T-DNA integration in orchid genotypes using PCR. 3) Analysis of transgenic plant leaf explants’ ability to produce somatic embryo in vitro. In vitro cultures were performed on the base medium of New Phalaenopsis (NP), plus various concentrations of TDZ (0, 1, 2 mg.L-1) and IBA (0, 1, 2 mg.L-1) or without TDZ and IBA as controls. The transgenic Phalaenopsis ‘Sogo vivien’ were transferred to pot mediums via ex vitro with two treatments: the first leaves were cut as explants for in vitro culture, and the plants were transferred to the mixture of fern medium with shavings of bark. The integration of T-DNA in the genome was detected by DNA genome amplification from the second leaves using the AtRKD4 gene primers and the POH1 gene. The results showed that the highest number of somatic embryo (SE) propagules or protocorm like bodies (PLBs) amounted to 27 were derived from transgenic plant # 2 cultured on NP + 2 mg.L-1 TDZ +1 mg.L-1 IBA medium. The presence of AtRKD4 transgenes were detected with the amplification of 380 bp of the RKD4 gene from the genome of transgenic plant # 2 by using PCR. There were 2 out of 15 plants that positively carry the AtRKD4 gene and produce SE. Thus, the stability of the AtRKD4 carrier T-DNA integration in the genomes of transgenic plants was 13.3%.